2014
DOI: 10.1177/0734371x13520460
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Incentives, Motivation, and Job Effort in the Public Sector

Abstract: What effects do financial incentives have on the effort made by public managers? How do different types of work motivation (i.e., intrinsic, extrinsic, and public service motivation) moderate this effect? We addressed these questions using experimental data from a sample of executives working for the Italian central government and found that monetary rewards had no significant effect on the intended effort of the study participants. Furthermore, the relationship between financial incentives and intended effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 81 publications
(199 reference statements)
1
56
0
Order By: Relevance
“…However, the effects of financial incentives are not always as expected (Gneezy, Meier, and Rey‐Biel ). For instance, recent studies in the field of public administration highlight that small economic incentives may have no effect at all, making them very inefficient (Bellé and Cantarelli ; Voorberg et al ), and that economic incentives can crowd out prosocial motivation (Bellé ).…”
Section: Policy Instruments To Stimulate Behavior Changementioning
confidence: 99%
“…However, the effects of financial incentives are not always as expected (Gneezy, Meier, and Rey‐Biel ). For instance, recent studies in the field of public administration highlight that small economic incentives may have no effect at all, making them very inefficient (Bellé and Cantarelli ; Voorberg et al ), and that economic incentives can crowd out prosocial motivation (Bellé ).…”
Section: Policy Instruments To Stimulate Behavior Changementioning
confidence: 99%
“…In the context of PA, an economic incentive takes on the characteristics of a paradox, faced with its re-statement by policy makers (especially in the USA) for over thirty years, the evidence offered by the literature is negative or at least ambiguous (Perry et al 2009). In particular, Belle and Cantarelli (2015) studying the effects of financial incentives on the effort made by public managers and how different types of work motivation (i.e., intrinsic, extrinsic, and public service motivation) can moderate these effects, and using experiments, found that monetary rewards had no significant effect on the managers' effort. Furthermore, the relationship between financial incentives and managers' effort, which was insignificant overall, was negatively moderated by the intrinsic motivation of the participants, positively moderated by extrinsic motivation, and unaffected by public service motivation.…”
Section: Literature and Main Research Questionsmentioning
confidence: 99%
“…Additionally, it has received increased attention in the public sector in the wake of New Public Management and public personnel reforms (Kellough, 1993;Kellough & Nigro, 2002. Some research finds that contingent rewards are ineffective in enhancing follower work effort (Belle & Cantarelli, 2014) and achieving high levels of trust (Jung & Avolio, 2000), while other research reports a positive relationship between contingent rewards and MTW (Butler et al, 1999;Dirks & Ferrin, 2002). Hence, there are competing theories and mixed findings about the effect of managerial rewarding behavior on MTW perception.…”
Section: H2: Emphasis On Internal Management That Relates To Making Cmentioning
confidence: 99%